2014
DOI: 10.4161/onci.28497
|View full text |Cite
|
Sign up to set email alerts
|

Secretory pathways generating immunosuppressive NKG2D ligands: New targets for therapeutic intervention

Abstract: Natural Killer Group 2 member D (NKG2D) activating receptor, present on the surface of various immune cells, plays an important role in activating the anticancer immune response by their interaction with stress-inducible NKG2D ligands (NKG2DL) on transformed cells. However, cancer cells have developed numerous mechanisms to evade the immune system via the downregulation of NKG2DL from the cell surface, including the release of NKG2DL from the cell surface in a soluble form. Here, we review the mechanisms invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 76 publications
2
59
0
Order By: Relevance
“…In the last decade, the releasing of soluble NKG2D ligands has been extensively investigated with regard to their contribution to tumor pathologies and associated with a worse prognosis among cancer patients. 45 This corollary could be responsible for a premature interaction of soluble tumor-derived ligands with various NCRs resulting in a receptor internalization and abrogated cytotoxicity mediated by various effector cell subsets. 46 Previously, a bi-national NK cell Phase I/II study (Clin-GovNo-NCT01386619) demonstrated the safety, feasibility, and tolerability of using allogeneic un-stimulated and IL-2-activated NK cells in patients with multiple relapsed leukemia and highly malignant solid tumors after receiving HSCT.…”
Section: E1055993-10mentioning
confidence: 99%
“…In the last decade, the releasing of soluble NKG2D ligands has been extensively investigated with regard to their contribution to tumor pathologies and associated with a worse prognosis among cancer patients. 45 This corollary could be responsible for a premature interaction of soluble tumor-derived ligands with various NCRs resulting in a receptor internalization and abrogated cytotoxicity mediated by various effector cell subsets. 46 Previously, a bi-national NK cell Phase I/II study (Clin-GovNo-NCT01386619) demonstrated the safety, feasibility, and tolerability of using allogeneic un-stimulated and IL-2-activated NK cells in patients with multiple relapsed leukemia and highly malignant solid tumors after receiving HSCT.…”
Section: E1055993-10mentioning
confidence: 99%
“…Indeed, soluble forms of NKG2DLs are present in the serum of cancer patients, and their levels correlate with tumor stage and metastasis (12,20,21,(38)(39)(40)(41), as well as with reduced expression of NKG2D on NK cells and other cytotoxic lymphocytes (11,21,42).…”
Section: Discussionmentioning
confidence: 99%
“…A more complete understanding of NK and sNKG2DL function in LAM pathogenesis could lead to development of NK-based interventional targets and perhaps inform treatment decisions in the future. Clinical trials that target NKG2DLs (58)(59)(60) in other neoplastic diseases are underway and may reveal strategies that could be successfully applied to LAM. Table 1).…”
Section: Discussionmentioning
confidence: 99%